ASSESSING THE AVAILABILITY OF SPORTS FACILITIES AND EQUIPMENT IN TRANSYLVANIAN SCHOOLS: A CROSS-SECTIONAL ANALYSIS - BALLA, Béla József; FARKAS, Gellérd (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: Physical education facilities and equipment represent a fundamental resource for ensuring effective teaching and learning in schools. Their availability and quality directly influence the conditions in which students participate in physical education. Objective: This study aimed to assess the availability and quality of physical education facilities and equipment in schools across Transylvania, Romania, in accordance with the national standards set by the Romanian Ministry of Education (order no. 3399/2017). Material and methods: A questionnaire was distributed to physical education teachers working in the region, collecting data on the presence, number, condition, and use of gymnasiums, sports halls, and outdoor physical education areas, as well as the quantity and perceived quality of sports equipment. Results: The results showed that most schools had one gymnasium (78.2%), while 7.3% had none. A significant positive correlation was found between the number of enrolled students and the number of indoor sports facilities. On average, one gymnasium served 457 students (sd = 309.37). A total of 92.7% of schools reported having suitable outdoor areas for physical education classes. 4did not meet the recommended quantities outlined by national regulations. While the quantity of equipment was insufficient, the perceived quality of facilities and equipment was generally rated as good. Discussion: These findings were consistent with previous research highlighting inequalities in the distribution of school infrastructure and resources. The reported adequacy of quality, despite quantitative shortages, reflected broader issues described in similar educational contexts. Conclusion: The findings highlight the need for targeted improvements in school infrastructure and resource allocation to support quality physical education.